Multifunctional antibacterial bioactive nanoglass hydrogel for normal and MRSA infected wound repair - Long Zhang; Wen Niu; Yuyao Lin; Junping Ma; Tongtong Leng; Wei Cheng; Yidan Wang; Min Wang; Jingya Ning; Shuanying Yang; Bo Lei (Journal of Nanobiotechnology, 2023)
Abstract Large-scale skin damage brings potential risk to patients, such as imbalance of skin homeostasis, inflammation, fluid loss and bacterial infection. Moreover, multidrug resistant bacteria (MDRB) infection is still a great challenge for skin damage repair. Herein, we developed an injectable self-healing bioactive nanoglass hydrogel (FABA) with robust antibacterial and anti-inflammatory ability for normal and Methicillin-resistant Staphylococcus aureus (MRSA) infected skin wound repair. FABA hydrogel was fabricated facilely by the self-crosslinking of F127-CHO (FA) and alendronate sodium (AL)-decorated Si-Ca-Cu nanoglass (BA). FABA hydrogel could significantly inhibit the growth of Staphylococcus aureus, Escherichia coli and MRSA in vitro, while showing good cytocompatibility and hemocompatibility. In addition, FABA hydrogel could inhibit the expression of proinflammatory factor TNF-α and enhance the expression of anti-inflammatory factor IL-4/ IL-10. Based on its versatility, FABA hydrogel could complete wound closure efficiently (75% at day 3 for normal wound, 70% at day 3 for MRSA wound), which was almost 3 times higher than control wound, which was related with the decrease of inflammatory factor in early wound. This work suggested that FABA hydrogel could be a promising dressing for acute and MRSA-infected wound repair. Graphical Abstract